Biologia populacional de uma nova espécie de Aeglidae (Crustacea, Anomura) na sub-bacia do rio Jaguari - RS - Legramanti, Rosemari Parisi (2011)
This study aims to evaluate some aspects of the biology of a new species of aeglid at Jaguari River basin (in process of description), such as the population structure, the morphological sexual maturity and somatic growth in natural environment. These investigations were conducted from November/2007 to October/2008, in a section of stream Perau in Jaguari county-RS. Monthly collections were made and individuals were captured in two ways, with the help of 25 traps trap, and these were arranged in the late afternoon of one day and removed in the following morning. The second method of sampling was a surber placed in the opposite direction to the stream flow so that with the revolving stones vegetation and all kinds of substrate and the animals were dragged into the capture equipment. The Surber sampling was made with a sampling effort of 30 minutes. The organisms collected were sexed based on the presence of pleopods in females and absence of those in males and / or position of the genital openings. Individuals had the following body dimensions measured with a digital caliper with 0.01 mm of precision: cephalothoracic length (CL), cephalothoracic width (CW), width of the second abdominal somite (AW), length of propodus chela left (LLC), length of propodus right chela (LRC) and height of the larger chelae (HC). After sexing and measurements the animals were returned to the same location that where collected. During working hours we sampled 1774 individuals (1259 males, 512 females and 03 individuals not sexed). Males and females were grouped into size classes of CL, where was observed a bimodal distribution. Males has significantly larger sizes than females, according to the Mann-Whitney (p<0,05). The sex ratio was significantly different from 1:1 in most sampling periods (p <0.05) when considering the general data (surber + trap), but followed the expected in most months sampled with Surber (p<0,05). The highest incidence of ovigerous females occurred in autumn (65.11%), followed by winter (5.81%) and spring (1.75%). Although the juveniles had been found in all seasons, the highest frequencies of these in relation to adults were observed in autumn (20.43%) and winter (17.29%). The smallest ovigerous female sampled in the field measured 10.45 mm of CL. The size of individuals at the beginning of morphological sexual maturity was estimated, using the program REGRANS, in 12.78 and 10.78 mm CL for males and females respectively. Males Aegla sp. n exhibit heterochely, with a preponderance of left chela laterality, while females have isoquelia. After the pubertal changes, an additional change in the level of allometry in relation to the dimensions of the chelae was detected in adult males. As a result, two groups of morphotypes in adult males, here designated as morphotype I and II were recognized according to the state of development of the chelipeds. The growth curves of the cephalothorax, estimated for males and females, are described by the following equations: Ct = 26,57[1 e -0,0064(t+18,14) e Ct = 21,71[1 e-0,008(t+30,25), respectively. Males reached larger sizes than females and showed higher growth rates than those. The estimated longevity for males was 670 days while that for females was 736 days. This study seeks to contribute to the knowledge of the biology of a new species of aeglid, it is expected that it can provide inputs for further research on these crustaceans and also direct efforts to preserve the species of the family Aeglidae and therefore all headwater areas where these animals live.